KREATIVITAS GURU DALAM MENGATASI KETERBATASAN SARANA DAN PRASARANA DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SEKOLAH DASAR - Muarif; Salahudin; Nasrullah; Rabwan Satriawan; Firdaus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to assess the level of teacher creativity in overcoming challenges related to limited facilities and infrastructure in the teaching of Physical Education, Sports, and Health (PJOK) at Ragi Public Elementary School. The research employs a descriptive qualitative approach. Data were collected from three PJOK teachers, the principal, and students through interviews focusing on measuring teacher creativity. The main instruments used in this study include semi-structured interviews, direct observation, and documentation. Thematic analysis was used to identify themes or patterns in the respondents' answers.The results of the study show that most PJOK teachers demonstrate a high level of creativity in addressing the lack of facilities and infrastructure. This is evident from various innovative strategies applied in the learning process, such as modifying sports equipment using simple materials, utilizing the surrounding environment as a learning medium, and implementing traditional game-based learning models that require minimal equipment. The findings also indicate that most teachers are able to foster student creativity through alternative teaching methods, creative use of technology, and exploration of the local environment as a learning resource. Therefore, it can be concluded that teacher creativity plays a crucial role in ensuring the quality of PJOK learning, even when faced with limited facilities and infrastructure.